Epileptic encephalopathy: Use and misuse of a clinically and conceptually important concept. (18th January 2016) - Howell, Katherine B.; Harvey, A. Simon; Archer, John S.
Summary: The term epileptic encephalopathy (EE) denotes a process by which epileptic activity adversely affects brain function over and above the underlying etiology. Underlying mechanisms are poorly understood, but recent studies demonstrate that seizures and interictal epileptiform discharges can disrupt distributed neural networks that underpin cognitive functions, both temporarily and permanently. EE is just one of a number of factors that can affect development in epilepsy. The presence and relative contribution of EE to cognitive impairment is often difficult to separate from that of the underlying etiology or even effects of antiepileptic medication (AEM). This difficulty has led to the increasing use of the term EE to encapsulate "severe" epileptic syndromes, or etiologies associated with severe epilepsy and intellectual disability (ID), regardless of evidence that the epileptic process has impacted cognition. The use of the term EE in the literature to describe both the process of cognitive impairment by epileptic activity and as a category for severe epilepsy syndromes is creating confusion. We propose that use of the term EE be restricted to the central concept of a pervasive epileptic process disrupting development, and that the use of EE as a classifier be avoided. A different term is needed to encapsulate the broad and heterogenous group of patients with severe epilepsy and ID, for which the mechanisms may be unknown but are often closely related to the underlying genetic, metabolic, or structural etiology. An improved understanding of the mechanisms by which EE develops is of critical importance, potentially leading to identification of biomarkers for early detection and treatment.